Availability and use of telehealth services among patients with ADRD enrolled in traditional Medicare vs. Medicare advantage during the COVID-19 pandemic - Wang, Nianyang; Seale, Melvin; Chen, Jie (Frontiers in Public Health, 2024)
Background: To examine the differences in telehealth availability and use among Medicare enrollees by Alzheimer’s Disease and Related Dementias (ADRD) status and Medicare Advantage (MA) versus Traditional Medicare (TM) enrollment surrounding the COVID-19 pandemic. Methods: This was a retrospective cross-sectional analysis of community-dwelling MA and TM Medicare enrollees with and without ADRD from the Medicare Current Beneficiary Survey (MCBS) Fall 2020 & Winter 2021 COVID-19 Supplement Public Use Files. We examined self-reported telehealth availability before and during COVID-19 and telehealth use during COVID-19. We used marginal effects from multivariable logistic regressions. Results: There were 13,700 beneficiaries with full-year MA (6,046) or TM (7,724) enrollment and 518 with ADRD and 13,252 without. Telehealth availability during COVID-19 is positively associated for enrollees with higher income (2.81pp [percentage points];95%CI:0.57,5.06), internet access (7.81pp; 95%CI:4.96,10.66), and owning telehealth-related technology (3.86;95%CI:1.36,6.37) while negatively associated for enrollees who are Black Non-Hispanic (-8.51pp;95%CI:-12.31,-4.71) or live in a non-metro area (-8.94pp; 95%CI:-13.29,-4.59). Telehealth availability before COVID-19 is positively associated for enrollees who are Black Non-Hispanic (9.34pp; 95%CI:3.74,14.94) and have MA (4.72pp;95%CI:1.63,7.82) while negatively associated with enrollees who are dual-eligible (-5.59pp;95%CI:-9.91,-1.26). Telehealth use is positively associated for enrollees who are Black Non-Hispanic (6.47pp;95%CI:2.92,10.01) and negatively associated with age 75+ (-4.98pp;95%CI:-7.27,-2.69) and female (-4.98pp;95%CI:-7.27,-2.69). Conclusions: Medicare enrollees with ADRD had similar telehealth availability and use compared to non-ADRD counterparts. MA enrollees had more availability to telehealth before COVID-19 but not during COVID-19 and did not use telehealth more during COVID-19 compared to TM enrollees.